NON-TRAUMATIC SPONTANEOUS ILEAL PERFORATION: EXPERIENCE WITH 125 CASES - Khalid, Sadaf; huq, Burhanul; Bhatti, Afsar Ali (Journal of Ayub Medical College Abbottabad, 2014)
Background: Non-traumatic ileal perforation is a common cause of obscure peritonitis in developing and underdeveloped world. The perforation of the ileum is one of the causes of peritonitis that is difficult to diagnose preoperatively. The objective of the study was to determine the increasing frequency of cases of non-traumatic ileal perforations and their subsequent management Methods: This descriptive case-series included 125 cases presenting in surgical emergency of Lahore General Hospital from 1st January 2014 to 1st December 2014. All patients were resuscitated and underwent emergency exploratory laparotomy. Results: The causes for perforation were enteric fever in 82 cases (65.6%), tuberculosis in 38 cases (30.4%), adhesions and other causes in 5 cases (4%).The main presenting symptom in all patients were severe abdominal pain associated with fever and abdominal distension. Perforations were surgically treated depending upon the number of perforations, general health status of patient and degree of fecal contamination. In total out of 125 cases, primary repair was done in 9 cases, resection and end to end anastomosis in 19 cases and in 13 patients' resection and ileotransverse anastomosis was done. In the case of 78 patients loop ileostomy was done and in 6 patients double barrelled ileostomy was performed. Conclusions: The incidence of terminal ileal perforations due to typhoid and the tuberculosis is high and carries high mortality and morbidity rates in delayed presentations. Therefore, it is high time now that general public health awareness should be created regarding food handling, sanitation and personal hygiene. Keywords: typhoid, terminal ileum, tuberculosis, perforations